Spinal epidural hematoma in an infant patient: a differential diagnostic of spinal cord compression syndrome - Felipe Gutierrez Pineda; Mauro Marcelo Suarez Marin; Daniela Perez Cadavid (Brazilian Society for Pediatric Neurosurgery, 2021)
A spontaneous spinal epidural hematoma is a collection of blood in the epidural space of the spine occurring in the absence of trauma or other pathological  blood conditions, this epidural blood clot has the risk to compress the spinal cord and impact negatively on the neurological outcome of the patients. With a low incidence on pediatrics this condition has not been studied deep, with difficulties on the clinical approach in infants and children due to the limitation in the pediatric neurological exam with the risk to be misdiagnosed. We describe a rare case of spinal cord compression on a young 14 month old patient with a spontaneous cervicothoracic epidural hematoma that presented with a ascending paralysis. Magnetic resonance imaging of the spine demonstrated an extensive epidural hematoma between C4 to T5 with spinal cord compression. An emergency laminectomy was performed with evacuation of the epidural blood clot with a total improve of the neurologic symptoms and without any residual hematoma following 3 months of the surgery. The spontaneous spinal epidural heamtoma is rare cause of spinal cord compression on infants and children with high risk of neurological impact without prompt diagnosis with MRI and emergent surgical evacuation.